Tactile and visual perception in radix augmentation with free fragmented cartilage in rhinoplasty - Fabiano Calixto Fortes Arruda (Revista Brasileira de Cirurgia Plástica, 2024)
Introduction: Correction of the nasal radix dorsum relationship has been carried out for several years using the most varied techniques such as auricular, septal, or costal cartilage grafts, filling with hyaluronic acid, use of fascia and grafts and the use of diced cartilage, silicone, and hyaluronic acid. The use of fragmented cartilage is described in the literature and has gained popularity in recent years, due to its ease of use. The objective of this study is to describe our experience with the use of fragmented cartilage graft in radix augmentation, comparing the patient’s visual and tactile perception and satisfaction. Method: Observational study in patients undergoing rhinoplasty from January 2018 to June 2022, in surgeries in which the radix was increased with the use of minced cartilage graft. Results: Of the 47 patients, the majority were female (35, 74.4%), with a mean age of 34.6 years (18-44). As for skin type, Fitzpatrick type 3 (n=28, 59.5%) was the main one, with patients with medium-thickness skin being frequently found (n=23, 48.9%). Complications present were infection (1 case), migration of chopped cartilage (3 cases), and partial resorption (1 case). In the assessment of tactile perception, 42 patients (89.3%) perceived cartilaginous prominences on palpation and only 2 (4%) visually. Satisfaction was high in 45 (96%) patients. Conclusion: Free minced cartilage can be used in the radix region with satisfactory results.